56.5k views
1 vote
F(-2) = -1 and g(1) = -2
(Fog)(1)

User Amitthk
by
5.0k points

1 Answer

6 votes

The value of the composite function fog(1) is -1

Explanation:

Step 1 :

Given,

f(-2) = -1

g(1) = -2

We need to find (fog)(1)

Step 2 :

Function f(2) means the value of the function f when x = 2

fog refers to composite function f(g(x)), that is evaluate the function g for x and then evaluate the function f for the result

So to find the composite function (fog)(1) we need to find g(1) first and then apply the function f on the result.

so g(1) = -2

f(g(1))=f(-2) = -1

fog(1) = -1

Step 3 :

Answer :

The value of the composite function is -1

User Brunov
by
4.7k points